OPTIMIZATION OF THE MATHEMATICAL MODEL OF THE GRADUATE EMPLOYMENT SYSTEM IN THE CONDITIONS OF THE DIGITAL ECONOMY - Khalikov Timur Tulkinovich (Labor economics and human capital, 2024)
In the article, the creation of a mathematical model to optimize the selection of vacancies for graduates in enterprises. A graphic model of the percentage of skills and grades acquired by graduates of higher education institutions in mastering subjects based on the curriculum was created using the semantic method.